2014
DOI: 10.1038/ajg.2014.94
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Non-Magnifying Narrow-Band Imaging in Screening of Early Esophageal Squamous Cell Carcinoma: A Prospective Comparative Study Using Propensity Score Matching

Abstract: OBJECTIVES:The usefulness of non-magnifying endoscopy with narrow-band imaging (NBI; NM-NBI) in the screening of early esophageal squamous cell carcinoma (SCC) and high-grade intraepithelial neoplasia (HGIN) remains unclear. Here, we aimed to compare NM-NBI and chromoendoscopy with iodine staining (CE-Iodine) in terms of the diagnostic performance, and to evaluate the usefulness of NM-NBI in detecting early esophageal SCC.METHODS:We prospectively enrolled 202 consecutive patients (male/female=180/22; median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 39 publications
3
91
0
2
Order By: Relevance
“…Recent advances in image‐enhanced endoscopy, such as NBI and LCE, enabled the early detection of esophageal cancer and dysplasia, which can be treated with endoscopic resection . NBI is a useful and noninvasive tool for detecting ESCN, with benefits of enhanced visualization of intrapapillary capillary loop patterns . LCE can be used to detect dysplastic lesions that go unnoticed with conventional WLE, which could alter the treatment plan for some patients .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in image‐enhanced endoscopy, such as NBI and LCE, enabled the early detection of esophageal cancer and dysplasia, which can be treated with endoscopic resection . NBI is a useful and noninvasive tool for detecting ESCN, with benefits of enhanced visualization of intrapapillary capillary loop patterns . LCE can be used to detect dysplastic lesions that go unnoticed with conventional WLE, which could alter the treatment plan for some patients .…”
Section: Discussionmentioning
confidence: 99%
“…When non-magnifying NBI was compared with iodine chromoendoscopy for the detection of oesophageal SCC, NBI demonstrated higher accuracy (77% vs 68%, P=0.03) and specificity (75.2% vs 64%, P=0.01) 95. In the opinion of the expert panel, IEE can achieve better delineation of the tumour extent for superficial oesophageal neoplasia.…”
Section: Consensus Statementsmentioning
confidence: 91%
“…Indeed, NBI seems to have a better sensitivity for superficial esophageal SCC when compared with WL imaging (97 vs. 55%, p < 0.01) [12-14]. Regarding the comparison between NBI and Lugol chromoendoscopy, three studies found that NBI and ME-NBI have an increased accuracy and specificity when compared with Lugol, although the sensitivity is similar between the two techniques [15-17]. These findings were also confirmed in two recent meta-analyses [18].…”
Section: Esophagusmentioning
confidence: 99%